Investigating the potential of Pulicaria jaubertii and Pulicaria petiolaris Herbs as promising functional food ingredients - Qais Ali Al-Maqtari; Amer Ali Mahdi; Norzila Othman; Jalaleldeen Khaleel Mohammed; Waleed Al-Ansi; Abeer Essam Noman; Adel Ali Saeed Al-Gheethi; Syazwani Mohd Asharuddin; Adnan Saeed (Cogent Food & Agriculture)
This study examined the nutritional, phytochemical, and bioactive profiles of Pulicaria jaubertii and Pulicaria petiolaris to establish their suitability as functional food additives. Generally, P. jaubertii exhibited a significantly higher protein and ash content (14.05 and 18.68 g/100 g DW). Conversely, P. petiolaris had higher fat, fiber, and carbohydrate content (3.9, 21.12, and 59.63 g/100 g DW, respectively). In physical investigation, P. jaubertii showed superior bulk density (0.29 g/cm³), tapped density (0.44 g/cm³), hygroscopicity (6.54%), solubility (14.62%), and water absorption capacity (533.42%). Volatile compound analysis found 267 in P. jaubertii, led by carvotanacetone (7.33%), and 371 in P. petiolaris, led by camphor (4.32%). The primary fatty acid constituents in both plants were palmitic and linoleic acids. Mineral analysis indicated P. jaubertii had greater magnesium, potassium, calcium, and iron (139.06, 437.47, 326.96, and 76.73 mg/100g DW, respectively). Leucine and aspartic acid were the most abundant free amino acids in both plants among the 18 essential and non-essential amino acids. Vitamin analyses revealed that P. petiolaris contained a higher B-complex, while P. jaubertii had more vitamin C. Interestingly, P. jaubertii exhibited the highest TPC (89.1 mg gallic acid equivalent/g DW), antioxidant activity (6.08 mg ascorbic acid/g DW), and antioxidant capacity (20.71 mg Trolox equivalent/g DW).